A study of medicinal plants used by Bajau community in Sepanggar Bay, Kota Kinabalu, Sabah / Nasyuha Jamian - Jamian, Nasyuha (2016)
This paper about the ethnobotanical study of medicinal plants that were used to treat diseases by Bajau communities in Sepanggar Bay, Kota Kinabalu, Sabah. This study conducted by collecting and recording the data by interviewing Bajau medicine man, and knowledgeable persons with the help of semi-structured and open ended questionnaire. The data that were documented are listed along with their indication, part used, form of preparation and route of administration. Then, the sample (claimed plants) were taken for further identification species. The results then further analysed in order to determine Informant Consensus Factor (ICF) and Fidelity Level (FL) of the plants on the basis of their use under various ailment categories. This study has documented 54 medicinal plant species from 41 families used for the treatment of 16 different ailment categories. The most frequently used plants part is leaves (47%) while decoction is the major form of preparation which is 40 percent. Afterwards, the dichotomous key of 54 medicinal plant consist of 1 Kingdom (plantae), 1 Division (Magnoliophyta), 2 Class (Liliopsida and Magnoliopsida), 9 Sub-class, 25 order, 41 family, 51 genus, 4 spesies. In terms of the Informant Consensus Factors index (ICF) showed that the local people tend to agree more to each other in term of the plants used to treat general health (0.88) and liver disorder (0.88). Meanwhile, the Fidelity Level index shows that Senna alata (L.) Roxb, Chromolaena odorata ( L . ) R.M. King & H. Rob. Terminalia catappa L and Orthosiphon aristatus (Blume) Miq were plants with the highest ICF value (100%). The ICF and FL values can be subjected to bioassay guided investigation and probably producing new drugs to treat disease for further study.